Application of exome sequencing to diagnose a novel presentation of the Cornelia de Lange syndrome in an Afro‐Caribbean family. Issue 8 (8th June 2020) - Thompson, Wayne; Carey, Patrick Z.; Donald, Tyhiesia; Nelson, Beverly; Bhoj, Elizabeth J.; Li, Dong; Hakonarson, Hakon; Ramirez, Maricela; Elsea, Sarah H.; Smith, Janice L.; Carey, John C.; Sobering, Andrew K.
Abstract: Background: Cornelia de Lange syndrome (CdLS) comprises a recognizable pattern of multiple congenital anomalies caused by variants of the DNA cohesion complex. Affected individuals may display a wide range of phenotypic severity, even within the same family. Methods: Exome sequencing and confirmatory Sanger sequencing showed the same previously described p.Arg629Ter NIPBL variant in two half‐brothers affected with CdLS. Clinical evaluations were obtained in a pro bono genetics clinic. Results: One brother had relatively mild proportionate limb shortening; the other had complete bilateral hypogenesis of the upper arm with absence of lower arm structures, terminal transverse defects, and no digit remnants. His complex lower limb presentation included long bone deficiency and a deviated left foot. The mother had intellectual disability and microcephaly but lacked facial features diagnostic of the CdLS. Conclusion: We describe a collaboration between a pediatrics team from a resource‐limited nation and USA‐based medical geneticists. Reports describing individuals of West Indian ancestry are rarely found in the medical literature. Here, we present a family of Afro‐Caribbean ancestry with CdLS presenting with phenotypic variability, including unusual lower limb abnormalities. The observation of this novel family adds to our knowledge of the phenotypic and molecular aspects of CdLS. Abstract : We found the same pathogenic NIPBL variant in two half‐brothers who are of Afro‐Caribbean ancestry. One of the brothers has a novel lower limb presentation.